Histogenesis of Prenatal Liver in Buffalo (Bubalus bubalis) - Singh, Opinder; Roy, K. S.; Kumar, Anoop (Indian Journal of Veterinary Anatomy, 2015)
The histogenesis of the liver was studied in buffalo foetii ranging from 1.50-92.0 cm curved crown rump length (CVRL). The developing liver at 1.50 cm - 4.0 cm CVRL occupied a large part of abdominal cavity and was surrounded by single layered connective tissue capsule. The parenchyma was comprised of hepatocytes andhaemopoietic cells. The initial hepatic lobulation and constituents of portal triad area was observed at 26.0 cm CVRL. The Kupffer cells appeared at initial stages whereas the islands of haemopoietic cells decreased with increase in gestational age.